Exploring vibrational spectra, electronic properties and thermal analysis of Isoguanine molecule using DFT - Bishwokarma, Nirmal; Budha, Chandra; Teemilsina, Nabin Kumar; Rai, Krishna Bahadur (Scientific World, 2025)
This study uses the density functional theory to describe the molecular structure, spectroscopic analysis, electronic properties and thermodynamic properties of the Isoguanine molecule. The Isoguanine molecule has an optimal energy of -542.683 Hartree (-14767.145 eV). The FT-IR spectra's peak values display the C-H, C=N, C=C stretching, CH in-plane bending, C-H out-of-plane bending, C-N stretching, C-N, and C=O vibration. HOMO-LUMO research reveals that the Isoguanine molecule has an energy gap of 4.180 eV. The electronegativity value of 3.782 eV represents the molecules' capacity to attract electrons and the chemical hardness value of 2.090 eV denotes molecular stability. The MEP (Molecular Electrostatic Potential) and ESP (Electrostatic Potential) investigations informed that the hydrogen atoms have electrophilic regions; the oxygen and nitrogen atoms have nucleophilic regions. The polarizability of the molecule is indicated by the softness value of 0.478 eV-1. Additionally, the chemical potential value, which denotes the capacity to give or receive electrons, is -3.782 eV. The electrophilic behavior that indicates its ability to receive electrons is also demonstrated by the electrophilic index, which has a value of 3.421 eV. H13 atoms have the largest positive charge, followed by C10 and all hydrogen atoms, while N6 has the highest negative charge, along with some negative charge on C8, C9, N2, N3, N4, N5 and O1 atoms. The molecule becomes hard due to the wider energy gap, and hardness is greater than softness. The thermodynamic parameters such as heat capacity at constant volume and pressure, internal energy, enthalpy, and entropy increase with temperature, whereas Gibbs free energy falls. This implies that the process becomes more thermodynamically favorable at higher temperatures, indicating increased spontaneity of the reaction.